Solving Heterogenous Fleet Capacitated Vehicle Routing Problem with Time Windows Using Cooperative Hybrid Firefly Algorithm - Ananda, Defri; Wirdianto, Eri; Alfandi, Rahmad (LPPM Universitas Andalas, 2025)
The Vehicle Routing Problem with Time Windows (VRPTW) is a widely studied logistics optimization problem, and its complexity increases when heterogeneous fleets are considered. This study proposes the application of the Cooperative Hybrid Firefly Algorithm (CHFA), an extension of the Firefly Algorithm, to solve the Heterogeneous Vehicle Routing Problem with Soft Time Windows (HVRPSTW). The mathematical model was implemented in Python, tested on benchmark datasets, and adapted to a fleet consisting of three vehicle types with different capacities to serve 100 customers. The proposed CHFA achieved feasible routing solutions with a total transportation cost of IDR 17.58 million and a computation time of only 30 seconds. These results demonstrate that CHFA can provide fast and efficient solutions for complex routing problems, making it highly applicable in logistics operations that demand quick decision-making and cost efficiency.